The Implementation of CIPP Model To Evaluate the Illiteracy Eradication Program for the Baduy Traditional Community in Banten Province - Harits Hijrah Wicaksana; Hendy Tannady; Indra Gunawan (Malikussaleh University, Aceh, Indonesia, 2025)
The purpose of this study is to use the CIPP (Context, Input, Process, Product) evaluation model to assess the literacy eradication program among the indigenous Baduy community. Interviews, document analyses, and program implementation observations were used to gather data. This study used a descriptive approach and a qualitative technique. The researcher explained how the literacy eradication effort for the indigenous Baduy population in Lebak Regency was put into action. In addition to discussing the context, input, process, and results of the implementation of the literacy eradication program for the Baduy indigenous community, the study participants also talked about the perceptions and roles of the Lebak Regency government in the education sector and community leaders in the implementation. In addition, observations in the Baduy area (Leuwidamar) and examinations of policy documents and literature were incorporated in the data-gathering process. According to the evaluation's findings, there are gaps in data across agencies, no clear rules, and difficulties implementing them because of local knowledge and the values of the Baduy community. As a foundation for policy development, this study suggests a non-formal education strategy grounded in local culture and more precise data collection. Without making any attempts at adaptive planning, the administration seems to be blaming the Baduy culture for its failure. Especially in indigenous areas, the program's execution has not yet met its full potential. The Baduy community does not have any unambiguous quantitative or qualitative measures of the program's effectiveness. Success evaluations are less substantial and more administrative. Furthermore, the notion that the Baduy group rejects education has been strengthened by false impressions about them.